V-notch to Prevent Sliding of Crimpable Hook - Gyawali, Rajesh; Pokharel, Praphat Ranjan; Shrestha, Gunjan Kumar; Giri, Jamal (Orthodontic Journal of Nepal, 2015)
En-mass retraction of anterior teeth most commonly involves the use of crimpable hooks which often dislodge when retracting force is applied. A V-notch distal to the hook may prevent such sliding when sandblasting and dental adhesives are not available